TRANSFORMASI PEMIKIRAN AL-GHAZALI DARI KECENDERUNGAN RASIONAL KE SUFISTIK (Telaah Kritis Epistemologi Sejarah Pemikiran) - Muhammad Endy Fadlullah; Fathi Hidayah (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2020)
Discussing the transformation of Al-Ghazali's thinking from rational tendency to sufistic is not as easy as al-Ghazali immediately changing the character of his thinking. This transformation process is very long. Over a long period of time, within al-Ghazali there was a transformation in his speculative interests, and even his outlook on life. He was not interested in philosophy anymore, and devoted himself entirely to Sufism and the renewal of orthodox Islamic teachings. In the aftermath of the psychological crisis and his escape in Sufism, he produced a book that became a magnum opus for al-Ghazali, Ihya' Ulum Al-Din. However, he is still remembered and inspires Muslims afterwards especially in the matter of fiqh, theology, philosophy, and also sufism which became the conversion of the end point of his scientific imagination options. This research uses library research design and uses al-Ghazali's rational-sufistic epstemology historical approach with the theory of transformation in al-Ghazali's Intellectual history from rational to sufistic.